HPTLC Fingerprints of Alcoholic Extracts of Phyllanthus species collected from Various Parts of Eastern Ghats in Andhra Pradesh: Life Sciences-Botany for Medicinal scien - anna, S. Akkul; rareddy, P.Malleswa; araju, R.R. Venkat; Kumar, B.R. Chaitanya (International Journal of Life Science and Pharma Research, 2021)
The genus Phyllanthus L. consists of 750 to 850 species distributed in tropical and subtropical around the world while 51 species in India. Most of them have been used in traditional medicine since ancient times. Phyllanthus spp.. like P. amarus, P. debilis, P. fraternus, P.urinaria and P. virgatus are called bhumyamalaki, used in Ayurveda. More than 514 compounds have been isolated from Phyllanthus, the majority of which are lignins, triterpenoids, flavonoids, and tannins. Lignins like phyllanthin and hypophyllanthin have been shown hepatoprotective activity and tannins exhibit various biological activities. Corilagin, geranin, and gallic acid are another three most prevalent compounds in this genus. P.amarus shows high concentration of Phyllanthin than P. fraternus, P. virgatus, P. maderaspatensis, P. urinaria, and P. debilis. Our aim is toestablish physical constants and fingerprint profile of Phyllanthus species collected from various parts of Eastern Ghats in Andhra Pradesh using high performance thin layer chromatography (HPTLC) technique. It is one of the fast growing techniques, used to analyze the phytochemical constituents. Leaves of thirteen Phyllanthus species were used to prepare methanolic extracts. Extracted samples used for carrying out HPTLC. Sample was spotted on TLC plate as triplicate and developed the plate with the mobile phase as Toluene: Ethyl acetate: Methanol (7: 2: 1). Dried TLC plate was then scanned under the UV at 366nm. All the Phyllanthus spp.. exhibits significant fractions of phyllanthin, niranthin, quercetin and phenolic compounds in alcoholic extracts. It can be used as a diagnostic tool for the correct identification of potential Phyllanthus spp.. and it is useful as a phytochemical marker and also a good estimator of genetic variability in the plant populations.